Ecological-Agrochemical Land Evaluation and Classification under Organic Farming - GORB, Oleg; YASNOLOB, Ilona; CHAYKA, Tetyana; ZORIA, Oleksii; DUGAR, Tetyana; SHVEDENKO, Pavel; KALIAN, Oleksandr; LYPII, Yevheniia; PROTSIUK, Nataliia (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020, 2020)
In modern economic conditions, economic components must be based on environmental components, especially for agricultural production, which ensures economic and food security of the country. Therefore, management system of agricultural enterprises has to be supplemented with environmental and agro-chemical components in order to improve and increase soil quality. The peculiarities of ecological agrochemical farm lands’ evaluation and certification in Ukraine were considered in the article. Their necessity for farmlands used for manufacturing organic raw materials and products was determined. Land classification and characteristics according to the degree of suitability for manufacturing organic products and raw materials are given: suitable, limited suitable, unsuitable lands. Indices of soil suitability for organic farming and their standards have been studied, namely: humus content; topsoil depth; particle size distribution; reaction of soil solution; the sum of absorbed bases (Ca + Mg); soil density; the content of mobile compounds of phosphorus, potassium, micro- elements, easily hydrolyzed nitrogen, nitrogen by nitrification power and mobile sulfur in the soil. Emphasis is placed on land suitability for organic farming, as important direction of agricultural production eco-balance. Agro-technological measures to improve ecological and agro-chemical condition of the soil used in organic farming are presented, considering sanitary-hygienic condition of the soil, its ecological stability and agro-chemical soil fertility. Interdependence and responsibility of farmers for soil condition as a result of their economic activities, the expediency of forecasting possible contamination of crops grown in the future have been mentioned. It is emphasized that the received information is entered into the ecological passport of farms, which implies the manufacturing of organic crop growing and livestock farming products at the level of world standards. The influence of ecological-agrochemical condition of land under organic farming on the quality of raw materials and products was determined. Forecasting the quality of organic farm products and raw materials according to their biological full-value condition and environmental safety is carried out by assessing the groups of indicators: qualitative assessment of farm’s soil; ecological and agro-chemical certification of farm lands; environmental impact assessments of farming system and technologies of crop cultivation; ecological and agro-chemical assessment of lands for growing organic farm raw materials and products. Emphasis is placed on social responsibility of agricultural manufactures for products and soil quality. Thus, it is necessary to improve soil quality in Ukraine by introducing organic farming, which will ensure land management stabilization and strengthen their adaptability and enable to grow high-quality organic farm raw materials and products.